1992
DOI: 10.1007/bf00197040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four classes of herbicides on growth and acetolactate-synthase activity in several variants of Arabidopsis thaliana

Abstract: We have isolated a triazolopyrimidine-resistant mutant csrl-2, of Arabidopsis thaliana (L.) Heynh. Here, we compare csrl-2 with the previously isolated mutants csrl and csr1-1, and with wild-type Arabidopsis for responses to members of four classes of herbicides, namely, sulfonylureas, triazolopyrimidines, imidazolinones, and pyrimidyl-oxy-benzoates. Two separable herbicide binding sites have been identified previously on the protein of acetolactate synthase (ALS). Here, the mutation giving rise to csrl, origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 38 publications
3
35
0
1
Order By: Relevance
“…[5][6][7][8] In this study, we examined the inhibition of E. coli K-12 AHAS I using several herbicides, including the sulfonylurea derivatives chlorimuron ethyl (CE), chlorsulfuron (CS), metsulfuron methyl (MSM), sulfometuron methyl (SMM), pirimisulfuron (PSM), nicosulfuron (NS), bensulfuron methyl (BSM), and pyrazosulfuron ethyl (PSE), along with thifensulfuron methyl (TSM) and the imidazolinone derivatives imazapyr, imazethapyr, imazapic, and imazaquin. The structures of these herbicides have been published.…”
Section: Inhibition Of Ahas I By Herbicidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In this study, we examined the inhibition of E. coli K-12 AHAS I using several herbicides, including the sulfonylurea derivatives chlorimuron ethyl (CE), chlorsulfuron (CS), metsulfuron methyl (MSM), sulfometuron methyl (SMM), pirimisulfuron (PSM), nicosulfuron (NS), bensulfuron methyl (BSM), and pyrazosulfuron ethyl (PSE), along with thifensulfuron methyl (TSM) and the imidazolinone derivatives imazapyr, imazethapyr, imazapic, and imazaquin. The structures of these herbicides have been published.…”
Section: Inhibition Of Ahas I By Herbicidesmentioning
confidence: 99%
“…3,4) AHAS is the site of action of sulfonylurea, imidazolinone, triazolopyrimidine, and pyrimidylbenzoate herbicides, [5][6][7][8] which might operate by binding to the regulatory site on the enzyme. 7) AHAS activity is found in bacteria, fungi, and plants, and is contributed by one or more isozymes.…”
mentioning
confidence: 99%
“…AHAS is the site of action of four different classes of herbicide ; sulphonylureas, imidazolinones, triazolopyrimidines and pyrimidyl(oxy)benzoates [5][6][7][8]. These herbicides may bind to the regulatory site on the enzyme [7].…”
Section: Introductionmentioning
confidence: 99%
“…In plant and yeast AHAS there is a proline residue at the equivalent sequence position, and mutation to serine results in herbicide resistance [6][7][8][9][10][11]. Moreover, Mazur and Falco [5] reported that the S100P (Ser"!!…”
Section: Introductionmentioning
confidence: 99%
“…An imidazolinone-resistant mutant of A. thaliana AHAS has been isolated [10,12,13] and shown to contain a mutation of S653 to asparagine. The apparent K i for imazethapyr of this mutant is 1.9 mM [4], very similar to that of wild-type E. coli AHAS II (0.78 mM).…”
Section: Introductionmentioning
confidence: 99%